2017
DOI: 10.3390/nu9050470
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious Metabolic Effects of High Fructose Intake: The Preventive Effect of Lactobacillus kefiri Administration

Abstract: Modern lifestyle and diets have been associated with metabolic disorders and an imbalance in the normal gut microbiota. Probiotics are widely known for their health beneficial properties targeting the gut microbial ecosystem. The aim of our study was to evaluate the preventive effect of Lactobacillus kefiri (L. kefiri) administration in a fructose-rich diet (FRD) mice model. Mice were provided with tap water or fructose-added (20% w/v) drinking water supplemented or not with L. kefiri. Results showed that prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 71 publications
(98 reference statements)
2
28
0
1
Order By: Relevance
“…In agreement with other reports, we also found an increase in inflammatory markers (IL-6, IL-1β and TNFα) and a decrease in anti-inflammatory markers (CD206: M2 marker and IL-10 ) in EAT from FRD mice [31,[47][48][49][50]. Moreover, adipocytes isolated from FRD mice showed an inflammatory response (higher IL-6 release) that worsened when the obese phenotype was more evident (FRD 10 weeks).…”
Section: Accepted Manuscriptsupporting
confidence: 92%
See 3 more Smart Citations
“…In agreement with other reports, we also found an increase in inflammatory markers (IL-6, IL-1β and TNFα) and a decrease in anti-inflammatory markers (CD206: M2 marker and IL-10 ) in EAT from FRD mice [31,[47][48][49][50]. Moreover, adipocytes isolated from FRD mice showed an inflammatory response (higher IL-6 release) that worsened when the obese phenotype was more evident (FRD 10 weeks).…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…Although the deleterious effects of fructose diet are milder when compared to high fat diet, we and many other authors observed that obesity by chronic fructose intake induced metabolic disorders that got worse when time of consumption was extended [12,13,31,46].…”
Section: Accepted Manuscriptmentioning
confidence: 59%
See 2 more Smart Citations
“…Glucose intolerance was to some extent prevented by supplementation of Lactobacillus kefiri treatment changed Bacteroidetes and Firmicutes profiles. It was demonstrated that the administration of Lactobacillus kefiri prevents the deleterious effects of fructose-rich diet intake, therefore improved metabolic disorders [101].…”
Section: Management Of Lactose and Glucose Intolerancementioning
confidence: 99%